1981
DOI: 10.1080/00039896.1981.10667601
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Dioxide Water Disinfection: A Praspective Epidemiology Study

Abstract: An epidemiologic study of 198 persons exposed for 3 months to drinking water disinfected with chlorine dioxide was conducted in a rural village. A control population of 118 nonexposed persons was also studied. Pre-exposure hematologic and serum chemical parameters were compared with test results after 115 days of exposure. Statistical analysis (ANOVA) of the data failed to identify any significant exposure-related effects. This study suggests that future evaluations of chlorine dioxide disinfection should be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…C102 associated kinetics of red cell GSH depletion and intravascular hemolysis in rats and chickens was reported by Abdel-Rahman et al (6). More recently, Michael et al (11) of this laboratory published results of a prospective epidemiology study, showing the absence of clinicopathological effects in human volunteers to C102 treatment of their community water supply. In addition, the effects of C102 and metabolites, as they effect the cellular GSH system in the rat, mouse and chicken blood, were investigated by Couri et al (8) Oxidative in vitro damage to erythrocytes by NaCl02 was reported 48 BERCZ ET AL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C102 associated kinetics of red cell GSH depletion and intravascular hemolysis in rats and chickens was reported by Abdel-Rahman et al (6). More recently, Michael et al (11) of this laboratory published results of a prospective epidemiology study, showing the absence of clinicopathological effects in human volunteers to C102 treatment of their community water supply. In addition, the effects of C102 and metabolites, as they effect the cellular GSH system in the rat, mouse and chicken blood, were investigated by Couri et al (8) Oxidative in vitro damage to erythrocytes by NaCl02 was reported 48 BERCZ ET AL.…”
Section: Introductionmentioning
confidence: 99%
“…Frozen serum samples from 350 human volunteers of the prospective epidemiology study previously reported by Michael et al(11) were in our possession. Samples were selected on the basis of medical history of the volunteers.…”
mentioning
confidence: 99%
“…Frozen serum samples from 350 human volunteers of the prospective epidemiology study previously reported by Michael et al (11) were in our possession. Samples were selected on the basis of medical history of the volunteers.…”
Section: Thyroid Function Test On Human Seramentioning
confidence: 99%
“…Reported effects of NaClO 3 poisoning in humans include cyanosis, methemoglobinemia, renal failure, and renal congestion. Human epidemiology studies investigating doses of NaClO 3 more relevant to those found in drinking water have not identied any signi cant exposure related effects (27)(28)(29)(30)33). A prospective epidemiology study was conducted on 197 volunteers during a 12-week period when the primary water disinfectant in the community was changed from chlorine to ClO 2 .…”
Section: Introductionmentioning
confidence: 99%